Pain is a Prevalent Symptom of Adolescents at Diagnosis with Postural Orthostatic Tachycardia Syndrome - Elizabeth Bettini; Robin R Fabian; Jeffery P Moak (Open Journal of Pain Medicine - Peertechz Publications, 2017)
Pain is often endorsed by patients with postural orthostatic tachycardia syndrome (POTS). A retrospective chart analysis of adolescents diagnosed with PTS from January 2014-December 2015 at the pediatric cardiology clinic at Children's National Health System were reviewed. 93% of the subjects reported pain at the time of diagnosis, with 46% of the sample reporting more than one site of pain. Since chronic pain syndromes and POTS are associated by similar symptom burden and often develop after illness or injury, both may be a product of pathology stemming from neuroinfl ammation and neuralplasticity that results in central sensitization and autonomic nervous system dysfunction.